Pengaruh Etika Wajib Pajak terhadap Kepatuhan Wajib Pajak dengan Pengetahuan Wajib Pajak sebagai Variabel Moderating (Studi Kasus Wajib Pajak Orang Pribadi yang terdaftar di KPP Pratama Garut) - muslim alkausar (Jurnal Wacana Ekonomi, 2018)
This study aims to determine the effect of Taxpayer Ethics on Taxpayer Compliance with Taxpayer Knowledge as a Moderating Variable at KPP Pratama Garut. The sample size of 81,604 taxpayers in 2017 as a population is determined using the Slovin formula with a sample size of 100 respondents with respondent characteristics, namely: Gender, Age, Last Education, Type of Work, and Income. The data analysis method is simple linear regression analysis and moderated regression analysis. Based on the results of simple linear regression calculations, it shows that taxpayer ethics has a positive and significant effect on taxpayer compliance at Garut Pratama Tax Office. Meanwhile, based on the results of the moderation regression calculation, it shows that the taxpayer's knowledge can moderate the effect of taxpayer ethics on taxpayer compliance at Garut Tax Office.